Rapid Geological Change Challenges Concepts of Sustainability - Berger, Antony (Geoscience Canada, 2007)
SUMMARY Many landscapes are subject to biophysical change on the time scale of a normal human life. Despite a common belief that if the human footprint were absent, natural landscapes would be in benevolent stasis, such rapid changes have frequently affected human history; also, they have implications for environmental attitudes and policies. Now, when human influences on the environment are greater than ever and threaten to overwhelm natural systems, a re-examination of non-human change, and particularly those earth processes that cause harm, may be instructive. Scanning the voluminous literature on sustainable development, it is hard to find discussions of natural disasters and rapid geological change. There is an opportunity for earth scientists to contribute to the search for a clearer concept and its application. Looking at physical landscapes in terms of their potential for continuity and for providing natural resources can offer fresh perspectives on the complex idea of sustainability.